People's approach towards agricultural funds in the Gheorgheni Region - György Katalin Takács; Gizella Madaras (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
After five years of Romania's accession to European Union, there have taken part several changes in Romanian economy, especially in agriculture. All participants of agriculture and food industry have to exist in a new, changing environment. There are numbers of applications opened for agricultural producers, but many of them are not able to obtain, they are unsuccessful often, and there are serious problems in calling the financial budget pro-rata. In this study we examined the activity of producers for European Union's subsidies in Harghita County between 2007-2011, which priority goals were identifiable, that will show the characteristics of the future's development of agriculture for the coming years. We focused on the role of vocational training and the role of qualification among the applicants. We assumed that in the second half of the CAP period, it will increase - not only the numbers of submitted applications - but the demand for those trainings, that give such qualifications and knowledge that are requirements of the authorities. We carried out a structured deep interview personally the notoriety of the subsidy projects, the qualification, the background of applicants, their intentions why they took part in the projects in Gyergyó Region et cetera.
Keywords: 330; Rural area; Agriculture; Funds; Adult Education; Self-sufficiency